Decisions concerning communication modes and the influence of travel time : a situational approach - Tillema, T; Dijst, M; Schwanen, T (Pion, 2010)
In this paper we examine the tradeoff between face-to-face (F2F) communication and a telephone call in the situation where people consider discussing something important but not urgent with a good friend located at a distance. In so doing we extend previous studies of communication behaviour in two ways. We develop and employ a situational approach to communication mode choice inspired by time geography and attitude theory and we devote particular attention to the sociopsychological mechanisms driving communication mode decisions. As a consequence, we can analyse the effects of travel time in the physical world on communication choices via and in combination with those of a person’s attitudes, perceptions, desires and past behaviours. Our data collected from Dutch single-earner and dual-earner households suggest that travel time mediates the effects of goal desire, past behaviour and perceived time pressure. When the travel time increases, respondents with a strong desire to discuss something important but not urgent trade a preference for F2F contact for a telephone conversation. Those who have frequently used the telephone in a similar situation before have a lower intention to conduct an F2F conversation but only when the travel time is short. Finally, we see that time-pressured respondents are more inclined to use the telephone when the travel time is longer, presumably because F2F communication involves more time in that situation.